Current Research and Development of Carbon–Hydrogen (C–H) Activations in Catalyzing Organic Syntheses - Yu, Jin-Gang; Wang, Zhi-Hang; Liu, Qi; Chen, Xiao-Qing; Jiang, Xin-Yu; Jiao, Fei-Peng (Current Organic Synthesis, 2015)
To generate series of useful compounds from hydrocarbons, various reactions which are able to satisfy these requests such as addition reactions to carbon/carbon multiple bonds, nucleophilic ring-opening reactions, carbonyl chemistry of the “non-aldol” type, cycloaddition reactions and so on have been studied in-depth. And in general, the preactivation of coupling synthons is always required for such cross-coupling methodologies. However, some existing downsides such as complicated processes and low efficiencies have kept the costs of the classical cross-coupling reactions very high. Due to its advantages such as higher yields of the desired product, relatively fewer byproducts and higher functional-group tolerance over the classical cross-coupling reactions, direct C-H functionalization is thought to be one of the most atom-economical synthetic processes. To develop better, faster, cheaper ways for converting the highly abundant hydrocarbons to value-added chemicals, carbon–hydrogen (C–H) activation is becoming one of the most powerful synthetic tools. As time goes on, C-H activation will find its wider application in a variety of catalytic processes in the pharmaceutical industry, materials science and other industries.
Keywords: C-H activation